Global associations of key populations with HIV-1 recombinants: a systematic review, global survey, and individual participant data meta-analysis - Nchinda, Nkazi; Elangovan, Ramyiadarsini; Yun, Jason; Dickson-Tetteh, Leslie; Kirtley, Shona; Hemelaar, Joris; , WHO-UNAIDS Network for HIV Isolation; Characterisation; Abimiku, Alash'le G.; Agwale, Simon; Archibald, Chris; Avidor, Boaz; et al. (Frontiers in Public Health, 2023)
Introduction Global HIV infections due to HIV-1 recombinants are increasing and impede prevention and treatment efforts. Key populations suffer most new HIV infections, but their role in the spread of HIV-1 recombinants is unknown. We conducted a global analysis of the associations between key populations and HIV-1 recombinants. Methods We searched PubMed, EMBASE, CINAHL, and Global Health for HIV-1 subtyping studies published from 1/1/1990 to 31/12/2015. Unpublished data was collected through a global survey. We included studies with HIV-1 subtyping data of key populations collected during 1990-2015. Key populations assessed were heterosexual people (HET), men who have sex with men (MSM), people who inject drugs (PWID), vertical transmissions (VERT), commercial sex workers (CSW), and transfusion-associated infections (BLOOD). Logistic regression was used to determine associations of key populations with HIV-1 recombinants. Subgroup analyses were performed for circulating recombinant forms (CRFs), unique recombinant forms (URFs), regions, and time periods. Results Eight hundred and eighty five datasets including 77,284 participants from 83 countries were included. Globally, PWID were associated with the greatest odds of recombinants and CRFs (OR 2.6 [95% CI 2.46–2.74] and 2.99 [2.83–3.16]), compared to HET. CSW were associated with increased odds of recombinants and URFs (1.59 [1.44–1.75] and 3.61 [3.15–4.13]). VERT and BLOOD were associated with decreased odds of recombinants (0.58 [0.54–0.63] and 0.43 [0.33–0.56]). MSM were associated with increased odds of recombinants in 2010–2015 (1.43 [1.35–1.51]). Subgroup analyses supported our main findings. Discussion As PWID, CSW, and MSM are associated with HIV-1 recombinants, increased preventative measures and HIV-1 molecular surveillance are crucial within these key populations. Systematic review registration PROSPERO [CRD42017067164].